ENVIRONMENTAL TAXATION IN ALGERIA BETWEEN DETERRENCE AND INCENTIVE MECHANISMS FOR PROTECTING THE ENVIRONMENT - Youssef Henka,; Douadi Ibrahim,; Hamidatou Salah, (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to identify the tax laws and regulations related to the environmental taxation that were approved in the Algerian tax legislation starting from the year 1992 in order to protect the environment. The study used the descriptive approach when addressing the basic concepts about the environment and sustainable development, and then identifying environmental taxation which is a deterrent and motivational mechanism to control environmental behavior. The study concluded that the tax system in Algeria worked to protect the environment through the enactment and application of environmental taxes and fees that have a motivational effect and a deterrent effect.